Gallstones in Elderly Patients: Impact of Laparoscopic Cholecystectomy - A Montori; M Boscaini; M Gasparrini; G Miscusi; L Masoni; M Onorato; J Montori (Canadian Journal of Gastroenterology)
The use of laparoscopic cholecystectomy (LC) in elderly patients may pose problems because of their poor general condition, especially of cardiopulmonary function. Moreover, these patients present with acute cholecystitis and associated common bile duct stones more often than their younger counterparts. From 1990 to 1999, the authors performed 943 LCs; 31 (3.2%) were attempted on elderly patients, 11 (35%) of which were on an emergency basis because of acute cholecystitis, cholangitis or acute biliary pancreatitis. Ten per cent of LCs needed to be converted to an open cholecystectomy, most often because of an increase in the partial pressure of carbon dioxide in the blood produced by excessive operative time. A gasless procedure was used in the last three years of the study on eight cases; the overall rate of conversion from LC to open cholecystectomy in this group was 0%. Associated gallbladder and common bile duct stones were found in five (16%) patients (four preoperative LC endoscopic sphincterotomy and one transcystic approach). The success rate in both of these cases was 100%, overall morbidity was 29% and there was no mortality. These results show that LC is a feasible and safe procedure for use in elderly patients. Gasless LC should be preferred in patients classified as American Society of Anesthesiologists’ class III because an excessive duration of operation is the most common reason for converting to an open cholecystectomy.